Efektivitas Komite dan Mekanisme Tata Kelola Perusahaan terhadap Pencegahan Kejahatan Keuangan - Alice Alice; Natalis Christian (Politeknik Ganesha Medan, 2022)
Abstract The research objectives of this study are to analyze the effectiveness of committee and mechanism of corporate governance to prevent financial crime. Financial Crime often occur inside the company, especially in Indonesia. Financial crime covers fraud, money laundering, bribe, corruption, terrorist financing and so on. At 2018, there’s case where PT. Garuda Indonesia committed revenue recognition fraud by recognizing revenue amounted to USD 239 million from Mahata Aero Teknologi which is yet to be received by the end of 2018. The company’s management and external audit are fined for the negligent in preventing the fraud. Therefore, the effectiveness of company’s organizational structure played a big role to supervise and prevent the occurrence of financial crimes. In this discussion, the author investigates the effectiveness of audit committee, board of commissioners, stand-alone risk committee, external audit, effect of managerial ownership and company’s performance toward financial crime. Data for the research were collected from secondary data found in annual report of 426 companies and analyzed using logistic regression method using SPSS 25. The study findings prove that stand-alone risk committee, external audit, and company’s performance have a significant negative effect toward financial crime, while size of audit committee have a significant positive effect toward financial crime. Research show that meeting frequency of audit committee, board of commissioners, and managerial ownership has no significant effect toward financial crime